Deep-seated fragmentation, transport of breccia dikes and emplacement: An example from the Borborema province, northeastern Brazil. (March 2015) - Ferreira, Valderez P.; Sial, Alcides N.; Weinberg, Roberto F.; Pimentel, Marcio M.
Abstract: Three syenite dike sets, named the Santa Cruz dikes, are coeval with the 627 ± 13 Ma old porphyritic calc-alkalic Princesa Izabel granitoid, northeastern Brazil. Dike set 1 is up to 1.5 m wide, strike 030–040 Az, roughly parallel to the regional foliation. Dike set 2 strikes 120°–130 Az and consists of xenolith-bearing syenites and is roughly parallel to dike set 3, which is up to 1.5 m wide and consists of xenolith-rich syenites forming matrix-supported breccias. Xenoliths in dike sets 2 and 3 are usually up to 3 cm long, angular to sub-rounded, tend to be evenly distributed and occupy ∼50% of the volume of dike set 3. They are amphibolite, mica-pyroxenite and diorite from deep source, and gneiss and feldspar xenocrysts from the conduit. The large amount of dense ultramafic/mafic xenoliths in the breccia dikes indicates rapid ascent of the host magma. The calculated natural viscosity, based on whole-rock chemical data, is 680–4600 Pa.s for 2.3 wt% water and temperatures from 1000 to 900 °C, respectively. A minimum ascent rate of ∼0.3 m/s is estimated from the settling velocity of a 30 cm-long diorite xenolith, the largest one, and an initial fraction of xenoliths of 5%. Progressive addition of xenoliths to the magma during its ascent increased the viscosity of the liquid–solid mixture during emplacement, and this would imply a Bingham rather than Newtonian behavior. These xenoliths were formed by early fracturing of wall rocks during dike propagation associated with thermal spalling of the wall rocks, by intrusion of magma along dike-parallel fractures during the development of a sequential conjugate pair of shear zones. Xenoliths are abundant not only because these magmas have ascended rapidly and could transport them, but also because the initial low viscosity of the magma promoted intense fracturing of the conduit. Highlights: We describe coeval dikes carrying xenoliths: free, bearing, and xenoliths-rich dikes. Mechanism of rock fragmentation and transport is discussed. Xenoliths have been formed by deep-seated mechanism of fragmentation.